(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
The decay of isotope has been studied using a detector calibration , with an overall energy resolution . Angular distributions have been obtained for the tow transitions and states of . Comparison between the structures of low-lying states and , the ratio , the transition , and deformation parameter of this nuclei with the even-even nickel isotopes , , , , , is made and with some authors nucleus in the region where the neutrons number and considered magic numbers. The data have been analyzed with the Shell Model.